Sex Hormone Status in Women with Rheumatoid Arthritis - Hülya Ergül Kazıl,; Banu Arslan Şentürk,; Serdar İpek,; Korhan Bayram,; Füsun Üstüner, (Archives of Rheumatology, 2007)
Objective: Sex hormones seem to play an important role as modulators and perpetuators of rheumatic disorders with autoimmune involvement such as rheumatoid arthritis (RA). The aim of this study was to investigate the levels of sex hormones in patients with RA. Patients and Methods: In this study we measured the serum total testosterone (TT), dehydroepiandrosterone- sulfate (DHEA-S), follicle stimulating hormone (FSH), luteinizing hormone (LH), progesteron, prolactin (PRL) and estradiol levels of 26 patients with RA and compared with 22 healthy control subjects. All hormone parameters concentrations were determined by electrochemiluminesans assay on Elecsys®Systems E170 Modular Analytics autoanalyser using commercial kits (Roche Diagnostics GmbH, Mannheim, Germany). Results: The patients with RA presented significantly decreased values of FSH, DHEA-S, progesterone ve TT levels (p=0.03, p< 0.001, p=0.03, p<0.001, respectively) with respect to the control group. Estradiol levels were also higher in RA group (27.92±13.1 pg/ml) compared with control subjects (21.17±11.4 pg/ml) but the difference was not significant (p>0.05). Upon comparison of the RA and control groups, the RA group had significantly higher levels of PRL (p<0.001). There were insignificant correlations between hormone levels and clinical data in patients (p>0.05). Conclusion: Our results support the hypothesis that sex hormones may be a risk factor for the development of RA. For definitive role of sex hormones in RA further studies are needed. (Rheumatism 2007; 22: 84-7)